A família de pessoa com autismo e o cuidado na perspectiva do aconselhamento pastoral - Martins, Marcelo (2012)
This dissertation has as research object the family with an autistic child and as the Pastoral Counseling can contribute as support in a situation like this, or similar. Search with this study to have a better understanding of the issue of the autism, through the report of a case, and intend to understand the ways that The Pastoral Counseling has shown to help in cases like these. The first chapter presents the actual situation of a family that, notes through diagnosis that your child is suffering from autism. Thus, is described as is contact with this reality-note that the child is suffering from autism. In the second chapter are investigated three concepts: autism, family and care. With respect to the concept of autism, a study on definition, history and diagnosis, to understanding of this subject that not yet so is explored. Later, it is approached question of the family, with emphasis on the feelings and crises that involve a family with a child s autism. Finally, it presents the issue of care. The purpose of the second chapter is to establish a tripod, that will be necessary to the sequence of the research. The third chapter presents The Pastoral Counseling as a reference for support in cases like that will approached in the first chapter. The third chapter presents The Pastoral Counseling as a reference for support in cases like that will be addressed in first chapter. The chapter begins with some definitions, then it is talking about the biblical and theological foundations of Pastoral Counseling and their historical roots and, subsequently, is appointed as Pastoral Counseling can help and contribute to restoration of families deep crises is given emphasis at this part Systemic Pastoral Counseling. The fourth and last chapter presents some possibilities that Pastoral Counseling can offer help to families with a child with autistic. It presents some notes on the contribution of spiritual help to the family and church family that experiences the reality of autism.